2010
DOI: 10.3109/00048670903446882
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) to Investigate Group and Gender Differences in Schizophrenia and Bipolar Disorder

Abstract: The RBANS highlighted the cognitive deficits in schizophrenia and BD patients compared to controls and also each other. There were no overall gender differences in cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
5
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 56 publications
6
30
5
1
Order By: Relevance
“…Compared with other studies with the RBANS, our scores were higher than those of the normative sample of people with schizophrenia (Wilk et al, 2004) and more in line with those found in other studies (Becker, Bond, Mueser& Torrey, 2007;Gogos, Joshua &Rossell, 2010;Han et al, 2012;Loughland et al, 2007), but the differences were probably to do with the composition of the samples studied (outpatient or inpatient care, employment programs, etc.). Our results also showed a strong association of the RBANS score with educational level, which is usual but not always found in other studies (Loughland et al, 2007) and particularly between paid work and good cognitive functioning (Bell & Bryson, 2001;Giugiario et al, 2012;McGurk & Mueser, 2004).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Compared with other studies with the RBANS, our scores were higher than those of the normative sample of people with schizophrenia (Wilk et al, 2004) and more in line with those found in other studies (Becker, Bond, Mueser& Torrey, 2007;Gogos, Joshua &Rossell, 2010;Han et al, 2012;Loughland et al, 2007), but the differences were probably to do with the composition of the samples studied (outpatient or inpatient care, employment programs, etc.). Our results also showed a strong association of the RBANS score with educational level, which is usual but not always found in other studies (Loughland et al, 2007) and particularly between paid work and good cognitive functioning (Bell & Bryson, 2001;Giugiario et al, 2012;McGurk & Mueser, 2004).…”
Section: Discussionsupporting
confidence: 69%
“…It is essential to design effective educational programs to compensate for their lack of academic experience. In turn, the fact that the variable "sex" (woman) enters the equation which predicts ordinary employment must be related to the lower neuropsychological deficit, better progression and less negative symptomatology which seems to affect women with schizophrenia (Gogos et al, 2010;Ramsay et al, 2012), it may also be related to the specific employment opportunities found in Andalusia. Similar correlates between sex (being women), high educational level and competitive employment have been found in previous studies (Waghorn, Saha & McGrath, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Not all studies however support a therapeutic effect of testosterone; other studies showed no improvements with testosterone treatment in post-menopausal women (Kocoska-Maras et al 2011;Moller et al 2010). Nevertheless, given that cognitive deficits in schizophrenia have been consistently reported and are considered the most debilitating and intractable symptoms of schizophrenia (Aleman et al 1999;Gogos et al 2010a;Saykin et al 1994), it is possible that testosterone treatment may improve cognition in women with schizophrenia. In the present study, we therefore aimed to examine the effect of testosterone treatment on drug-induced PPI disruption in female rats (aim 3).…”
Section: Introductionmentioning
confidence: 94%
“…For example, much of the emotional prosody recognition research in BD has (1) used patients as psychiatric controls, or grouped them with patients diagnosed as having another affective or psychotic disorder (Edwards et al, 2001;Hofer et al, 2010;Murphy and Cutting, 1990;Rossell et al, in press), (2) given little attention to the impact of mood state or diagnostic subtype, (3) failed to conduct well powered investigations of gender effects despite growing evidence of a female advantage for cognitive functions including emotional prosody recognition in both healthy (Donges et al, 2012;Kret and De Gelder, 2012;Schirmer et al, 2002;Szymanowski et al, 2007) and other psychiatric populations (Barrett et al, 2008;Bozikas et al, 2006;Carrus et al, 2010;Gogos et al, 2010), and (4) failed to examine linguistic processing, or control for potential deficits in the processing of auditory information which could provide insight into whether reported patient difficulties reflect an emotion specific deficit or a generalized auditory problem(see Van Rheenen and Rossell, 2013 for a review).…”
Section: Introductionmentioning
confidence: 98%